The Use of EnergySaving Ultraviolet Electrical Equipment in Agriculture - L. Yu. Yuferev (Сельскохозяйственные машины и технологии)
It was noted that the optical radiation in the ultraviolet (UV) range plays an important role in agricultural production, and a lack of it leads to the deterioration of animal productivity.Research purpose The study aims to substantiate the parameters of energy-saving agricultural electrical equipment operating in the ultraviolet range.Materials and methods The study shows that it is possible to create a universal therapeutic irradiator based on LEDs with a wavelength of 310 nanometers. The calculation methods are given. The parameters of UV devices for premises disinfection are substantiated. It has been found out that UV radiation increases the polymerization rate of paint coatings and facilitates the creation of energy-saving optical insect traps.Results and discussion The paper provides some examples of own-developed energy-saving systems and their use for the therapeutic irradiation of animals. The replacement of LE-30 fluorescent lamps with LEDs has resulted in a 13-fold reduction in electricity consumption. It has been found out that the use of bactericidal irradiators in poultry houses reduces not only the concentration of microorganisms but also the content of carbon dioxide and ammonia. The use of own-developed irradiators for photochemical polymerization of paint coatings reduces the curing time by 2 times. Optical insect traps have been created based on LEDs with a wavelength of 385 nanometers and the best pulsation frequency of the light source has been determined at 100 hertz.Conclusions The equipment has been developed and the parameters for irradiators operating in the range of 254-390 nanometers were substantiated for a variety of their applications in agriculture.